The effects of phytase and xylanase supplementation on performance and egg quality in laying hens. Issue 5 (3rd September 2018) - Taylor, A. E.; Bedford, M. R.; Pace, S. C.; Miller, H. M.
ABSTRACT: 1. The aim of this study was to evaluate the effects of phytase and xylanase and their interaction on laying hen performance, egg quality, phosphorus (P) digestibility, phytate breakdown, volatile fatty acid (VFA) production and peptide YY concentration. 2. Two hundred and forty hens were allocated to cages at 22 weeks of age based on a 3 × 2 arrangement with phytase (0, 300 or 1500 FTU/kg) and xylanase (0 or 12 000 BXU/kg) as factors. 3. Phytase increased hen-day production ( P  < 0.05), daily egg mass ( P  < 0.05) and P digestibility with increasing levels of phytase ( P  < 0.001). Phytase fed at 1500 FTU/kg reduced IP6 and IP5 and increased myo-inositol concentration in gizzard digesta ( P  < 0.05). Phytase fed at 300 FTU/kg reduced IP6 in ileal digesta ( P  < 0.05); however, IP6 and IP5 were further reduced and myo-inositol increased when phytase was added at 1500 FTU/kg ( P  < 0.05). 4. Xylanase improved feed efficiency when phytase was fed at 300 FTU/kg ( P  < 0.05). In the absence of phytase, xylanase reduced dry matter and Ca digestibilities ( P  < 0.05). 5. Neither phytase nor xylanase had an effect on peptide YY or caecal VFA concentrations.